Sepsis-associated encephalopathy and septic encephalitis: an update. Issue 2 (1st February 2021) - Tauber, Simone C.; Djukic, Marija; Gossner, Johannes; Eiffert, Helmut; Brück, Wolfgang; Nau, Roland
ABSTRACT: Introduction: Sepsis-associated encephalopathy (SAE) and septic encephalitis (SE) are associated with increased mortality, long-term cognitive impairment, and focal neurological deficits. Areas covered: The PUBMED database was searched 2016–2020. The clinical manifestation of SAE is delirium, SE additionally is characterized by focal neurological symptoms. SAE is caused by inflammation with endothelial/microglial activation, increase of permeability of the blood-brain-barrier, hypoxia, imbalance of neurotransmitters, glial activation, axonal, and neuronal loss. Septic-embolic (SEE) and septic-metastatic encephalitis (SME) are characterized by focal ischemia (SEE) and small abscesses (SME). The continuum between SAE, SME, and SEE is documented by imaging techniques and autopsies. The backbone of treatment is rapid optimum antibiotic therapy. Experimental approaches focus on modulation of inflammation, stabilization of the blood-brain barrier, and restoration of membrane/mitochondrial function. Expert opinion: The most promising diagnostic approaches are new imaging techniques. The most important measure to fight delirium remains establishment of daily structure and adequate sensory stimuli. Dexmedetomidine and melatonin appear to reduce the frequency of delirium, their efficacy in SAE and SE remains to be established. Drugs already licensed for other indications or available as food supplements which may be effective in SAE are statins, L-DOPA/benserazide, β-hydroxybutyrate, palmitoylethanolamide, and tetracyclines or other bactericidal non-lytic antibiotics.